EFEKTIVITAS PENGGUNAAN BAJU KATETER TERHADAP TINGKAT KEMUDAHAN DAN KENYAMANAN BERAKTIVITAS PADA PASIEN DENGAN TERPASANG KATETER (Nursing Sciences Journal, 2024)
Outpatients with urinary disorders generally receive procedures like catheter insertion. Patients with a catheter often find it difficult to perform activities, including outpatient care. Therefore, there is a need for catheter clothing to facilitate and provide comfort for patients when active, even with a catheter in place. This study aims to determine the effectiveness of catheter clothing on the ease and comfort of activity in patients with a catheter. This research uses a quantitative method, with a Pre-Experimental with a cross-over design approach. The sample in this study was outpatients with a catheter who could perform activities/mobility independently or with assistance. There were 23 respondents, with the sample collection technique being random sampling. Data analysis used the Mann-Whitney Test. This study showed a significant difference indicating ease and comfort of activity between regular clothing and catheter clothing, with a value of z = -5.830, p = 0.001, and r = -1.21. This suggests a significant effect in the difference in ease and comfort between regular and catheter clothing. Conclusion : Using catheter clothing effectively increases ease and comfort in outpatients with urinary disorders who have a catheter in place. Keywords : Catheter Clothing, Outpatients, Catheterized Patients, Ease, Comfort